Concurrent Autoreceptor-Mediated Control of Dopamine Release and Uptake during Neurotransmission: An In Vivo Voltammetric Study - Wu, Qun (J Neurosci, 2002)
Receptor-mediated feedback control plays an important role in dopamine (DA) neurotransmission. Recent evidence suggests that release and uptake, key mechanisms determining brain extracellular levels of the neurotransmitter, are governed by presynaptic autoreceptors. The goal of this study was to investigate whether autoreceptors regulate both mechanisms concurrently. Extracellular DA in the caudate–putamen and nucleus accumbens, evoked by electrical stimulation of the medial forebrain bundle, was monitored in the anesthetized rat by real-time voltammetry. Effects of the D(2) antagonist haloperidol (0.5 mg/kg, i.p.) on evoked DA levels were measured to evaluate autoreceptor control mechanisms. Two strategies were used to resolve individual contributions of release and uptake to the robust increases in DA signals observed after acute haloperidol challenge in naive animals: pretreatment with 3β-(p-chlorophenyl)tropan-2β-carboxylic acidp-isothiocyanatophenylmethyl ester hydrochloride (RTI-76; 100 nmol, i.c.v.), an irreversible inhibitor of the DA transporter, and kinetic analysis of extracellular DA dynamics. RTI-76 effectively removed the uptake component from recorded signals. In RTI-76-pretreated rats, haloperidol induced only modest increases in DA elicited by low frequencies and had little or no effect at high frequencies. These results suggest that D(2) antagonism alters uptake at all frequencies but only release at low frequencies. Kinetic analysis similarly demonstrated that haloperidol decreasedV(max) for DA uptake and increased DA release at low (10–30 Hz) but not high (40–60 Hz) stimulus frequencies. We conclude that presynaptic DA autoreceptors concurrently downregulate release and upregulate uptake, and that the mechanisms are also independently controlled during neurotransmission.